The Urgency of Extending the Term of Office of the Village Head in Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 concerning Villages - Tindoo, Sri Yatni; Djafar, Marwan; B, Sumiyati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study discusses the Urgency of Extending the Term of Office of the Village Head in Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages. The purpose of this study is to analyze the legal basis as well as the juridical and sociological implications of the policy of extending the term of office of village heads from six years to eight years. The method used is normative legal research with a legislative and conceptual approach. The results of the study show that juridically, the term of office extension policy is intended to create stability in village government, strengthen the effectiveness of development implementation, and reduce political conflicts and the cost of holding village head elections. However, in terms of democracy and governance, this policy raises new problems such as legal uncertainty, weak supervisory mechanisms, and potential abuse of power. Sociologically, term extensions can strengthen social stability, but they also risk prolonging the dominance of village elites and inhibiting leadership regeneration. Therefore, the urgency of this policy can only be justified if it is followed by strengthening the system of accountability, transparency, and community participation in village government.